Copper oxides for energy storage application: Novel pulse alternating current synthesis. (January 2018) - Ulyankina, A.; Leontyev, I.; Maslova, O.; Allix, M.; Rakhmatullin, A.; Nevzorova, N.; Valeev, R.; Yalovega, G.; Smirnova, N.
Abstract: Copper oxide powders (CuOx ) were reported to be electrochemically obtained under pulse alternating current by a facile and inexpensive one-pot method. The effect of the synthesis conditions on the copper electrode oxidation rate and product morphology and composition was studied. The CuOx products were characterized by X-ray powder diffraction (XRD), Raman spectroscopy, X-ray absorption near-edge structure (XANES) spectroscopy, energy dispersive spectroscopy (EDS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Depending on the synthesis conditions, the powders reveal different morphologies and composition, such as Cu2 O octahedra, Cu2 O decorated with CuO or Cu2 O-CuO bilayered composite. Cyclic voltammetry and charge-discharge measurements were used to study the electrochemical energy conversion properties of the materials. The results of the electrocatalytic study indicate that the powder with Cu2 O-CuO bilayered polyhedra is suitable for use in methanol oxidation; and the powder with Cu2 O octahedra has shown a good specific capacitance for supercapacitors.